Dilematis Mengenai Konsep Bussines Judment Rules di Badan Usaha Milik Negara Indonesia: Sudut Pandang Hukum Perusahaan - Bathari Qonita (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Problems in business activities always approach the directors of BUMN. Many of the directors of this State-Owned Enterprise have a central role in economic development in Indonesia. The state does business through BUMN so that it can always prioritize national and national interests. When the directors of a company commit acts that are detrimental to the state, it is often associated with a crime. Even though this aspect of the directors' decision falls into the scope of civil affairs. The purpose of this research is to find out the position of SOEs in the Indonesian legal system and the problems of the Business Judment Rules concept in company law and Indonesian national law. The results of this study indicate that the position of BUMN as a business institution is different from other corporate institutions in terms of the objectives to be achieved. In addition, the juridical problems that occur still show the existence of a blurring of norms and rules of law and have a negative impact on company management, especially the directors of a company. The conclusion of this study shows that the implementation of BJR is still far from the applicable provisions and produces maximum results. Keywords: Implementation; Business Judgment Rules; BUMN.